The Social Lives of Networked Students Mediated Connections - Kanagavel, Rajee; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines the social networks of international students, exploring the ways in which they experience social support and the role of the continuously evolving media landscape in their experiences of mobility. Drawing on survey data collected from over 250 respondents around the world, Rajee Kanagavel offers a social network analysis of transnational social formations to investigate the flow of social support through media channels, shedding light on how co-presence is no longer influenced by geographical distance. Kanagavel analyses the ways in which communication technologies are transforming the way we build and maintain relationships, and our ability to receive or give support across distance. As such, the book will be useful to scholars and students of sociology and media studies, particularly those with an interest in transnationalism, new media, social support and international student mobility.
1 Introduction. - 2. From a Network Theory to a Social Phenomenon -- 3. New Agency of Personal Communities -- 4. Network Constituents: Exploring Contents -- 5. Network Patterns: Combining Features -- 6. Determinants of Social Support -- 7. Conclusion.
Keywords: Mass media; Social media; Communication; International education .; Comparative education; Media Sociology; Social Media; Media and Communication; International and Comparative Education